Nilutamide pneumonitis: a report on eight patients. Issue 8 (August 1992) - Pfitzenmeyer, P; Foucher, P; Piard, F; Coudert, B; Braud, M L; Gabez, P; Lacroix, S; Mabille, J P; Camus, P
Abstract : BACKGROUND: Nilutamide is a new, specific synthetic antiandrogen, released in several countries for the treatment of metastatic carcinoma of the prostate. Eight patients at the University Medical Centre at Dijon and affiliated referring hospitals developed reversible pulmonary opacities and respiratory symptoms while taking the drug. METHODS: Records of eight patients who developed new, otherwise unexplained chest opacities while taking nilutamide were reviewed. In each patient a careful aetiological search was made for other environmental or endogenous causes. Six patients underwent bronchoalveolar lavage, and lavage fluid was cultured. Corticosteroids were not given, unless gas exchange was compromised (two patients). RESULTS: The eight patients (all male) had had carcinoma of the prostate diagnosed on average 10.2 months earlier. All had improved with nilutamide, with a dramatic decrease of prostate specific antigen levels. Seven had received nilutamide at the recommended dosage of 150 mg/day, and one had received twice that amount. Treatment had lasted on average 113 (range 10-225) days, and the mean cumulated exposure was 21.8 (3-38) grams. The chest radiographs showed bilateral infiltrates, with no consistent topographic predilection. A restrictive lung defect was present in six patients and hypoxia in all (mean arterial oxygen tension (PaO2) 6.6 kPa). Bronchoalveolar lavage showed lymphocytosis in four patients and neutrophilia in two. The outcome was favourable in all patients after they had stopped nilutamide only (five patients), with corticosteroids (two patients) or a simple reduction of nilutamide from 300 to 150 mg/day (one patient). Recovery was associated with improvement of pulmonary function and PaO2. CONCLUSION: Nilutamide is associated with interstitial pneumonitis in about 1% of patients and appears reversible.